Public Financing Conditions Faced by Micro-Enterprises of the Trade Sector in Costa Rica - Avendaño Quesada, Cristel (2017)
The main objective of the present assignment is to analyze the conditions of public financing that the microenterprises of the commerce sector in Costa Rica confront. For that, we analyze previous studies on the subject and select a sample of microentrepreneurs from the commerce sector, located in Heredia’s city. It investigates the degree of access to credit of microentrepreneurs, main constraints, institutions and funds that have been created, with their respective requirements.Also, the work shows how access to financing is key to the growth and expansion of these companies, so that the State should emphasize the promotion of this sector.